Penguatan Literasi Digital Melalui Alih Tekhnologi Program Kampus Mengajar di SD Al Mufidah Surabaya - Agus Wahyudi; Tatik Muflihah; Tharisa Putri Andriani; Aldi Setiawan (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The basic literacy that must be possessed by someone to be able to compete in the 21st century is literacy, numeric literacy, scientific literacy, digital literacy, financial literacy, and cultural literacy and citizenship. This community service activity aims to develop digital literacy for teachers and students through the Teaching Campus program at Al Mufidah Elementary School Surabaya. The Teaching Campus Program is one of the implementations of the Independent Campus Policy which is beneficial for students. This community service activity at SD Al Mufidah Surabaya is carried out from March 1, 2022 to June 25, 2022. The method of activity consists of four stages each week, namely: planning weekly activities with the team, implementing weekly activity plans, analyzing weekly activities, making improvement plans and follow-up. The form of digital literacy development activities is that students help teachers and students in implementing technology, information and communication (ICT) based learning. Students assist teachers and students in optimizing the use of various digital applications, namely WhatsApp, Zoom Meeting, Google Meet, Google Drive, and Google Form. Students also assist teachers in preparing teaching materials in the form of power point media (ppt) and learning videos. Thus, the Campus Teaching program is beneficial for students to gain hands-on experience in the field about becoming professional teachers, teachers and students also gain information and skills in using various digital technologies as a provision to face global competition in the 21st century.